Pemetaan Potensi Objek Wisata Menggunakan Sistem Informasi Geografis - Arianto Arianto; La Harudu; La Ode Nursalam; La Ode Amaluddin (Jurnal Penelitian Pendidikan Geografi, 2025)
Kulisusu District has great potential in the tourism sector because several types of tourist attractions such as natural, cultural, and artificial, can be visited. However, these tourist attractions are not widely known by the local and national community. The objectives of this research are: 1) to find out an overview of the potential tourist attractions in Kulisusu District, North Buton Regency; 2) to produce a map of the distribution of potential tourist attractions in Kulisusu District, North Buton Regency. This type of research is qualitative descriptive research with observation methods. The data analysis technique used in this research is a descriptive analysis and spatial analysis approach. The research results show that: 1) there are 9 potential tourist attractions in Kulisusu District consisting of 3 types of tourist attractions, namely natural tourism, cultural tourism, and artificial tourism; 2) potential tourist attractions in Kulisusu District are spread across 6 villages/subdistricts including Bangkudu Village, Eelahaji Village, Kadacua Village, Wasalabose Village, Linsowu Village and Malalanda Village.